THE TRANSITIVITY OF COVID-19 HOAX DISCOURSE IN INDONESIAN MEDIA - Rego Yasendalika; Sawirman Sawirman; Rina Marnita (Universitas Muhammadiyah Tapanuli Selatan, 2020)
In this study, the author analyzed the transitivity process of the Covid-19 hoax discourse in the Menkominfo's hoax report released on May 2, 2020. The theory used was the transitivity system proposed by Halliday (2014). The data is the hoax of Covid-19 that attacks various parties, such as: China, people of Chinese descent, the Indonesia, people in Indonesian government positions, attacking products and businesses, attacking community and religious organizations, and attacking other nations and individuals. The results of research on the Covid-19 hoax data that attack various parties include the use of verbal and nominal groups that have negative connotations. There are three types of Transitivity processes from the 15 data analyzed, namely: 7 material processes, 5 relational processes, and 3 verbal processes.